THE EFFECT OF ECONOMIC GROWTH, HUMAN DEVELOPMENT INDEX AND LABOR FORCE PARTICIPATION RATE ON POVERTY IN ACEH PROVINCE - Yurina Yurina; Maghfiratun Misla (LPPM Universitas Malikussaleh, 2023)
The purpose of this research is to find out how much influence economic growth, human development index (IPM) and labor force participation rate (TPAK) have on poverty in Aceh province. The data used in this study were obtained from the Central Bureau of Statistics for the province of Aceh for the 2006-2020 period. The data analysis method used in this study is multiple linear regression using the Eviews 10 program. The results of this study indicate that partially the economic growth variable has a negative and significant effect on poverty in Aceh Province, while the human development index variable (IPM) has a positive effect but not significantly to poverty in Aceh Province, and the variable labor force participation rate (TPAK) has a negative and significant effect on poverty in Aceh Province. As for simultaneously the variables of economic growth, human development index (IPM) and labor force participation rate (TPAK) have a positive and significant effect on poverty in Aceh Province.